Values, beliefs and economic behaviors: a regional approach - Joao Lopes; Jo\~ao Carlos Graça (European Regional Science Association (ERSA), 2012)
The main goal of this paper is to identify relationships between value orientations, beliefs and economic behavior of agents, on one side, and differences between levels of economic development, on the other. Empirical analysis is based on a sample of Portuguese municipalities and correspondent parishes, organized in groups set by an urban versus rural typology and according to levels of development as measured by GDP per capita. Different value orientations, beliefs and behaviors were identified according to mostly either supply-side or demand-side, as well as predominantly State versus Private Sector orientations. Four clusters were thereby considered, which we generically named as corresponding to 'stabilization', 'economic nationalism', 'entrepreneurship' and 'consumerism'. These clusters are related to spatial dimensions considered. Parishes named 'rural', 'rural-urban' and 'urban' have shown (albeit in a small degree) a prevailing orientation to the State, whereas 'developing' parishes lean to private sector. Rural parishes are markedly consumerist, whereas in those said 'rural-urban' supply-side orientation prevails. Both 'urban' and 'developing' (correspondent to zones going through big recent changes) occupy, in this context, an intermediate position.
Keywords: R29; Z13; 330; Values; beliefs; economic behaviors; Portuguese regions